2014
DOI: 10.3389/fnhum.2014.00417
|View full text |Cite
|
Sign up to set email alerts
|

Missing and Delayed Auditory Responses in Young and Older Children with Autism Spectrum Disorders

Abstract: Background: The development of left and right superior temporal gyrus (STG) 50 ms (M50) and 100 ms (M100) auditory responses in typically developing (TD) children and in children with autism spectrum disorder (ASD) was examined. Reflecting differential development of primary/secondary auditory areas and supporting previous studies, it was hypothesized that whereas left and right M50 STG responses would be observed equally often in younger and older children, left and right M100 STG responses would more often b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
71
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(82 citation statements)
references
References 55 publications
9
71
2
Order By: Relevance
“…seizures, aggression, anxiety, repetitive behaviors, language skills, or IQ. Another strategy is to employ proposed biomarkers, e.g., EEG gamma activity (Bosl et al 2011; Rojas and Wilson 2014), or delayed auditory responses (Edgar et al 2014). Parsing ASD symptoms into more tractable endophenotypes would further allow the use of animal models to illuminate genetic underpinnings and relevant molecular pathways.…”
Section: Discussionmentioning
confidence: 99%
“…seizures, aggression, anxiety, repetitive behaviors, language skills, or IQ. Another strategy is to employ proposed biomarkers, e.g., EEG gamma activity (Bosl et al 2011; Rojas and Wilson 2014), or delayed auditory responses (Edgar et al 2014). Parsing ASD symptoms into more tractable endophenotypes would further allow the use of animal models to illuminate genetic underpinnings and relevant molecular pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Reports have indicated that the ASD population exhibits elevated rates of brain stem or peripheral hearing dysfunction [13][14][15][16][17][18][19][20] and abnormalities in AEF components (i.e., cortical dysfunction) [1][2][3][4][5][6][7][8][9][10][21][22][23][24][25]. Intriguingly, research has indicated that individuals with ASD may present with peripheral auditory asymmetry [13], which may distort the cortical bilateral synchronization of AEF components in the central nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Altered auditory processing systems in children with ASD have been studied as neurological correlates of some phenotypes in ASD, such as inhibited language acquisition [1][2][3][4][5][6][7][8] and auditory hypersensitivity [9][10][11], and previous studies that have focused on auditory responses of the brain have also demonstrated altered cerebral laterality [2,5,6] and regional connectivity [12] in children with ASD. These studies have indicated alterations in cortical auditory processes in ASD [1,2,4,5,9,10], whereas increased rates of brain stem or peripheral hearing dysfunction have also been reported in the ASD population [13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations